Multi-State, Quasi-Experimental Study of the Impact of Internet-Based, On-Demand Professional Learning on Student Performance - Steven Shaha; Heather Ellsworth (Institute of Advanced Engineering and Science, 2013)
This multi-State, quasi-experimental study reflects the quantification of comparative gains in math and reading performance on standardized assessments. We contrasted performance in consecutive years pre-versus-post for students of teachers actively participating in an Internet-based, on-demand professional development (PD) program with their respective districts, thus normalizing for uncontrolled educational and socioeconomic variables. A random sample of 169 schools was analyzed representing teachers with a minimum high-participation level in PD. Results showed that students of participating teachers experienced 18.9% increases (p<.001) in math scores versus 4.2% (p<.01) for their districts, and 15.3% increases (p<.001) in reading versus 2.5% (p<.01) for their districts, equating to statistically significant 4.2 fold (p>.001) and 6.1 (p>.001) fold advantages, respectively. Findings support the high-participation use of Internet-based, on-demand professional learning for improving teacher effectiveness to impact student performance. DOI: http://dx.doi.org/10.11591/ijere.v2i4.3933